THE CORRELATIONAL STUDY OF ARTIFICIAL INTELLIGENCE IN EDUCATION ON STUDENTS’ OUTCOMES: A Study of Higher Education in Private University, Phnom Penh, Cambodia - By, Dr. Loeung; Ros, Dr. Paradise (Srawung: Journal of Social Sciences and Humanities, 2024)
Artificial Intelligence (AI) tool is very popular and essential for both teaching and learning activities in 21st century. While Artificial Intelligence (AI) has grown more widespread in education, its influence on student results is still debated. Some Cambodian universities have highlighted stresses about AI’s ability to stifle innovation and learning. This study aimed to assess students’ attitudes about AI and their perceptions of AI’s role in education, as well as the relationship between these characteristics and student outcomes.  Consequently, the aim of this research is to evaluate attitudes regarding Artificial Intelligence (AI) in education and views on the specific impact of AI on student achievements. Quantitative research was employed in the study, and this involved analyzing both descriptive and inferential data. Simple and multivariate regressions were utilized to assess the assess attitudes towards AI in education and specific perceptions in AI’s Role in education which impact on students’ outcomes. The study has designed accurate questionnaires to survey 222 individuals from higher education in private university in Cambodia. A regression study demonstrates that perceptions of AI’s Role in education have considerable impacts on students’ outcomes. The study’s findings indicate that perceptions about artificial intelligence’s role in education have major impacts on students’ achievements. This emphasizes the significance of instilling positive attitudes in pupils in order to get the benefits of AI in the classroom.